Legal Perspective: The Role of Infrastructure Guarantee Institution in Infrastructure Project Provision Through Public-Private Partnership Scheme (Faculty of Law, Universitas Negeri Semarang, 2022)
Infrastructure development is a strategic step for Indonesia to accelerate national development and economic equality. One of the efforts to attract investment is a partnership between the Government and Business Entities in the infrastructure provision. The large source of funding is one of the obstacles in infrastructure development and to overcome the funding gap in infrastructure development, a new financing scheme is used that involved new partners (private, non-profit organization, or the community) to participate in infrastructure financing and project implementation. The involvement of the Business Entity in infrastructure financing is carried out with the Public-Private Partnership (PPP) scheme. One of the Government's contributions to PPP is to provide Government Guarantees through Indonesia Infrastructure Guarantee Fund (IIGF). This study aims to examine the role of IIGF in the Public and how it functions to encourage the acceleration of infrastructure development. This study utilizes a normative juridical research method with a specification of descriptive-analytical. Results indicate that: from a legal perspective, IIGF is an institution that provides a guarantee for losses due to political risks such as changes in regulations, delays or failures of financial close, as well as failures in granting licenses and approvals. As an institution that provides a guarantee, IIGF is a development of a corporate guarantee whose legal basis uses the concept of a Recourse Agreement according to Civil Code but its implementation regulated in separate statutory regulations. IIGF performs a guarantee function and adds value to infrastructure development that has the greatest impact on the benefit of the people of Indonesia; protects the interests of the government in fulfilling infrastructure development through transparent and accountable processes; and increases investor trust by providing investment convenience and payment certainty for claims of risk of loss for a collaborative infrastructure project.